AN ANALYSIS ON GRAMMATICAL ERRORS IN SPEAKING COMMITTED BY THE ELEVENTH GRADE STUDENTS OF UNIT PERJALANAN WISATA (UPW) DEPARTMENT OF SMK NEGERI 1 SINGARAJA IN ACADEMIC YEAR 2015/2016 - ., Ni Nym. Ayu Padmitri; ., Prof. Dr.I Nyoman Adi Jaya Putra, MA; ., Dr. I Gede Budasi,M.Ed,Dip.App.Lin (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
Penelitian ini bertujuan untuk menganalisi jenis – jenis error dan sumber eror yang di dilakukan oleh siswa kelas XI Jurusan Unit Perjalanan Wisata di SMK Negeri 1 Singaraja tahun akademik 2015/2016. Penelitian ini merupakan jenis penelitian descriptif qualitatif. Penelitian ini menggunakan purposive sampling yang mana subjectnya terdiri dari 39 siswa dan 1 guru pengajar tour guiding. Data dikumpulkan melalui rekaman, membagikan kuesioner dan wawancara. Data dianalisis dengan cara mengidentifikasi error, mengklasifikasi error, menghitung error, menganalisis kuesioner dan hasil wawancara, melaporkan hasil analysis dan menarik kesimpulan. Hasil analisis menunjukkan bahwa terdapat empat (4) jenis eror, yakni omission, addition, misformation, misordering. Jumlah keseluruhan error adalah 861 error yang terdiri dari 41.8% omission errors, 30.5% misformation errors, 22.3% addition errors and 5.4% misordering errors. Berdasarkan hasil diskusi findings, wawancara dan kuesioner, sumber error terdiri dari intralingual dan interlingual error.Kata Kunci : errors, grammar, interlingual error and intralingual error This study aimed at analyzing the types and sources of errors committed by the eleventh grade students of Unit Perjalanan Wisata (UPW) Department of SMKN 1 Singaraja in academic year 2015/2016. This study is a descriptive qualitative research. This study used purposive sampling in which the subjects consisted of 39 students and 1 tour guiding teacher. The data were collected through recording, distributing questionnaire and interview. The data were analyzed by identifying the errors, classifying the errors, calculating the errors, analyzing the questionnaire and the result of the interview, reporting the result of the analysis and drawing the conclusion. The results of the study show that there are four types of errors committed by the students, namely omission, addition, misformation and misordering. The total numbers of errors are 816 which consist of 41.8% omission errors, 30.5% misformation errors, 22.3% addition errors and 5.4% misordering errors. Based on the discussion of the findings, interviews and questionnaires, the sources of errors are intralingual and interlingual error.keyword : errors, grammar, interlingual error and intralingual error